Security for software defined networks networking talks - Timms, Natalie; Safari eBooks ([S.l.] : Pearson Certification, 2014)
"30 Minutes of Video Instruction Overview Security for Software Defined Networks-Networking Talks provides you with practical advice and principles of security for and by Software Defined Networks. Description Security for Software Defined Networks-Networking Talks introduces security concepts that can be applied to SDN. The course starts with an overview of Software Defined Networking, examining what the architecture provides and detailing the various deployment models. Natalie Timms, CCIE Security, then provides an understanding of SDN and security, outlining how typical security considerations change when applied to an SDN. The course then dives a little deeper, detailing security for and by Software Defined Networks. Throughout this Networking Talk you will be introduced to concepts such as controller specific hardening, device hardening, network services, application and APIs, management and provisioning, communication channels, agent security services, and agent threat management. Major sections are as follows: Lesson 1-SDN Overview Lesson 2-SDN and Security Lesson 3-Security for the SDN Lesson 4-Security by the SDN Lesson 5-Summary"--Resource description page.
Title from resource description page (viewed May 5, 2014).
Presenter, Natalie Timms.
Keywords: Computer networks -- Security measures; Computer software -- Security measures; Electronic books